Elevating Environmental Literacy via InquiryBased Science Learning Strategies in UniversityLevel Pedagogy - Yusmar*, Firdha; Amrullah, Jadnika Dwi Rahmawan; Shilla, Rhischa Assabet; Firdausi, Soraya (Jurnal IPA & Pembelajaran IPA, 2025)
This study aims to test the effectiveness of inquiry-based science learning strategies in elevating students' environmental literacy compared to conventional learning strategies. The pretest-posttest control group is the chosen research design design, involving 60 students divided into an experimental group and a control group, each consisting of 30 students. Data were collected through environmental literacy tests, affective assessment using ELSA questionnaire (environmental literacy scale for adults), and skill assessment rubrics. Data analysis was conducted using SPSS software version 31 through normality tests, homogeneity tests, and paired t-tests. The results showed that both groups experienced significant improvements, but the experimental group demonstrated higher achievements after the intervention in all aspects. N-gain score of the experimental group was 0.64 compared to the control group at 0.35. The average posttest score of experimental group was 83.90 and control group was 70.47. The affective score of experimental group was 87.20 and control group was 85.17. The skills score of experimental group reached 85.53, control group was 76.96. The integrated environmental literacy score calculated from knowledge, affective, and skill aspects, was 85.53 for experimental group and 76.96 for control group, shows that experimental group was more dominant in very high and high categories, while control group was distributed across very high, high, and moderate categories. These results shows that inquiry-based science learning strategies are effective in elevating students' environmental literacy